Biology of fibrocartilage articular set against the functional demands - Gálvez, Luis H. (2005)
The functional demand of the temporomandibular joint requires an appropriate biological answer of the tissue that recaver the articular surfaces and the disk, which are interdependent in the functional and structural together with the synovial liquid The fibrocartilage has great copacity of rellular answer in front of the functional requirements, under conditions of normal load it is able to support and to dissipate the forces, however, in eventual loads that overcome the tisular tolerance it will break the homeostatic balance and the illness will begin. the nutritional deficiencies are the related factor with the dysfunctions articulate for deficiency or absence of the synovial liquid, altering the lubrication process The mechanical injury, also that it can limit the cellular functions and to alter the step of the nutrients by way of the synovial fluid, it produces liberation of free radicals that can be implied in the degradation of the Hialuronic Acid and the Prostaglandins production. The liberation catepsíns B and D for rupture of superficial chondrocytes, reviled lo the cartilage generating persistent inflammatory reactions. Other enzymes that participate in the degradation of cartilaginous matrix, bones, ligaments and tendons, are the metalloproteinase's, elaborated by chondrocytes by inductión of lnterleucin-1 o'clock, synthetized by macrophages during the ínflammation. the Alpha Necrosis Tumoral Factor (FNT), secreted by monocytes and macrophages, not only it acts as mediator of the inflammation, stimulating to synovials cells to the production of Prostaglandin, but it also induces to fibroblasts to synthetize Collagenaze that acts as mediator of the bony resorption.